OPTIMISING STUDENT INTEREST AND TALENT DEVELOPMENT THROUGH INTRACURRICULAR LEARNING OPTIONS AND THEMATIC PROJECTS IN THE MERDEKA CURRICULUM - Prisca Diantra Sampe; Aslan Aslan (Indonesian Journal of Education (INJOE), 2025)
This study aims to explore the optimisation of student interest and talent development through the selection of intraschool learning and thematic projects in the Merdeka Curriculum. The method used is a literature review, analysing various scientific references, books, policy documents, and research findings related to the implementation of the Merdeka Curriculum in schools. The Merdeka Curriculum provides freedom and flexibility to students to choose subjects, learning pathways, and involvement in thematic projects based on the Pancasila Student Profile, thereby facilitating the strengthening of students' interests and talents individually. Through a combination of adaptive intraschool learning and thematic projects based on collaboration and creativity, the development of students' potential is expected to be optimal. However, implementation in the field still faces challenges in terms of teacher readiness, facilities, assessment, and parent participation. This study highlights the importance of synergy among stakeholders as well as policy innovation and teacher training to ensure the success of interest and talent development in a dynamic, adaptive, and child-centred educational ecosystem.